Real-time Simulation of Cardiac Excitation Using Hardwareimplemented Cardiac Excitation Modeling - Mahmud, Farhanahani (International Journal of Integrated Engineering, 2012)
In this paper a hardware-implemented cardiac excitation model of a cardiac cell based on Luo-Rudy phase I (LR1) for the action potential (AP) generation in a mammalian cardiac ventricle is proposed to speed up the computational time during the simulation of the cardiac AP conduction. The hardware-implemented cardiac excitation model is designed by using analog circuits and a dsPIC microcontroller that could reproduce timedependent and time-independent nonlinear current-voltage characteristics of six-type of ionic currents in LR1 model. Through the study, real-time simulations of reentrant excitation conduction of cardiac cells are realized by coupling 30 active circuits of the cell models based on a cable model. The real-time simulations of initiation have been performed by the model and they are comparable to those from the LR1 model. Thus, it is conceivable that the hardware-implemented cardiac excitation model may be useful as one of alternative tools toward further understanding of the reentrant mechanisms.